Spectrophotometric determination of mercury with iodide and rhodamine B (Penentuan spektrofotometri untuk merkuri dengan menggunakan Rhodamine B dan Iodida) - Au, Yoong Yow Loo; Yap, Pei Lay; Muralithran G. Kutty,; Olaf Timpe, (Universiti Kebangsaan Malaysia, 2012)
Spectrophotometric methods for the trace amount determination of Hg(II) via extraction and polyvinylalcohol (PVAl) water stabilization was explored. The methods are based on the formation of ion-association complex of Hg(II) with Rhodamine B, [(HgI4)2-][(Rhodamine B)+]2 in highly acidic solution. Extraction using benzene showed the Beer’s law was obeyed for mercury(II) in the range of 5 to 27 μg Hg(II) / 20 mL of sample and molar absorptivity, ε = 17.68 × 104 L mole-1cm-1. For polyvinylalcohol (PVAl) stabilization method, Beer’s law showed the validity range of 10 to 120 μg Hg(II) / 10 mL of sample and molar absorptivity, ε = 16.84 × 103 L mole-1cm-1. The benzene-extraction method has been applied in assessing the performance of copper sulfide ion-exchanger in removing Hg(II). The result was comparable to the result obtained using cold vapor atomic absorption spectrometry (CVAAS).